1971
DOI: 10.1071/bt9710125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen source on growith of Eucalypts in sand culture

Abstract: Twelve species of Eucalyptus were grown in sand culture to determine their response to nitrate and ammonium nitrogen, and to different proportions of the two ions. Response was measured in terms of plant height, yields of plant parts (stems, branches, leaves, and roots), and number of branches. The results indicate a wide variation in the response of different species to form of nitrogen. A classification of species in terms of their overall response bears no relation to the accepted taxonomic classification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
1
9
1
1
Order By: Relevance
“…Santin et al (2014) evaluated the productivity of Ilex paraguariensis as a function of different N sources and observed that its preference for nitrogen source is dependent on the place of origin of the crop. A similar result was observed (Moore and Keraitis, 1971) who assessed the growth of 12 Eucalyptus species in relation to the N-NO 3-and N-NH 4+ and found that plants of ecological habitat similar tend to have similar responses in relation to the preferred source absorbed.…”
Section: Discussionsupporting
confidence: 63%
“…Santin et al (2014) evaluated the productivity of Ilex paraguariensis as a function of different N sources and observed that its preference for nitrogen source is dependent on the place of origin of the crop. A similar result was observed (Moore and Keraitis, 1971) who assessed the growth of 12 Eucalyptus species in relation to the N-NO 3-and N-NH 4+ and found that plants of ecological habitat similar tend to have similar responses in relation to the preferred source absorbed.…”
Section: Discussionsupporting
confidence: 63%
“…Growth responses are primarily to N (Moore and Keraitis 1971;Cromer and Jarvis 1990;Kirschbaum et al 1992), P (Kirschbaum et al 1992), or both in interaction (Halsall et al 1983;Fabião et al 1995); the main effects being increased shoot to root ratio, specific leaf area (SLA) and photosynthetic rate (Stoneman 1994). Improved soil nutrition was also shown to reduce seedling mortality of Eucalyptus incrassata seedlings by about 30% (Stoneman et al 1993).…”
Section: Introductionmentioning
confidence: 94%
“…comm. ), or to pH effects (Moore and Keraitis, 1971) . The pH of the sand did not change in the nitrate treatment so that pH alone could not explain the depression in yield .…”
Section: (Ii) Inorganic N Form and Growth Responsesmentioning
confidence: 99%
“…Little is known about the N requirements of E. globulus during this early growth stage . Furthermore, some forest eucalypt species are known to have a preference for ammonium-N rather than nitrate-N (Moore and Keraitis, 1971), although this can vary with the extent of mycorrhizal colonisation of seedling roots (Dell et al ., 1991) . The capacity of E. globulus to utilise high levels of nitrate-N is unknown, but this will be a significant factor determining N uptake where seedlings are planted on agricultural land .…”
Section: Introductionmentioning
confidence: 99%